The lotus unleashed : the Buddhist peace movement in South Vietnam, 1964-1966 - Topmiller, Robert J., 1948- (University Press of Kentucky, 2002)
During the Vietnam War, Vietnamese Buddhist peace activists made extraordinary sacrifices-including self-immolation-to try to end the fighting. They hoped to establish a neutralist government that would broker peace with the Communists and expel the Americans. Robert J. Topmiller explores South Vietnamese attitudes toward the war, the insurgency, and U.S. intervention, and lays bare the dissension within the U.S. military. The Lotus Unleashed is one of the few studies to illuminate the impact of internal Vietnamese politics on U.S. decision-making and to examine the power of a nonviolent movem.